Analisis Cara Pengenaan Biaya Disbursement Account dan Tingkat Pelayanan Kapal terhadap Daya Saing Perusahaan Keagenan Kapal di PT. Adhika Samudera Jaya - Hanny Amanda Rachmah; Faris Nofandi; Diyah Purwitasari (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The more rapid the development of the number of ship agency companies in Indonesia, the competition is also getting tighter. Therefore, ship agency companies must have a strategy to win the competition. One of the main factors to win the competition is the calculation of disbursement accounts and ship service levels. In the data taken, there is a relationship between the way disbursement account fees are charged and the level of ship service on the competitiveness of ship agency companies. Therefore, the author took the title